Statistical Confrontation of the Evolution of Tourism in the North East Region in Comparison with the other Regions of Romania - Gabriela Arionesei; Cristian-Valentin Hapenciuc; Mihai Costea (Amfiteatru Economic Journal, 2016)
The objective of this paper is the analysis of the tourist activity in the North East region, compared to the other development regions of Romania, throughout the period 1990-2014.. The research was performed through a system of tourism indicators applied in the Romanian regions, obtained from the National Institute of Statistics. This comparative analysis was carried out using the statistical method called ANOVA and the Post Hoc – Games-Howell test. In order to achieve the objective, our study implied the analysis of several relevant indicators for tourism: the accommodation capacity, the number of arrivals, the number of overnight stays, the length of stay and the net use of accommodation capacity index. Processing the data related to a period of twenty-five years, the analysis allowed to draw conclusions about the existence of differences between the values of indicators across regions. The comparative analysis of the available data reflected a number of differences between the North East region and the other regions of Romania, the North East region recording lower values for the analyzed indicators, while South East and Central regions hold significantly higher values than the other regions, for the majority of indicators.
Keywords: L83; R11; Z32; 330; regions; tourism indicators; ANOVA; comparative analysis; Post Hoc - Games Howell test